Married Monastics and Military Life: Contradictions and Conflicted Identities within South Korea’s Buddhist Chaplaincy System - Kyungrae Kim; Cheonghwan Park (Religions, 2020)
Since its modern origins in the Buddhist Purification Movement of the 1950s, South Korea’s Jogye Order has established monastic celibacy as central to its identity and claim to legitimacy as a Buddhist sect. However, in the order’s urgency to introduce Buddhist chaplains to the South Korean military in the 1960s, after almost two decades of Protestant monopoly over the chaplaincy program, the Jogye Order permitted its chaplains to marry; a practice which soon became the norm. This contradiction grew increasingly problematic for the order over subsequent decades and, in 2009, it attempted to resolve the issue by reversing the marriage exception for chaplains, reinforcing their identity as monastics within the order. While controversial, the resolution has proved effective in practice. However, this reversal has also provoked unprecedented lawsuits against South Korea’s Ministry of National Defense in 2017 and a ruling by Korea’s Human Rights Commission in 2018, challenging the Jogye Order’s exclusive control of the military’s Buddhist chaplaincies. Given the challenges these issues currently present to the Jogye Order’s chaplaincy program, this article interrogates the origins, history, significance, and impact of the issues surrounding the order’s marriage exemption for its military chaplains.